STUDY OF SINGLE ROW AND DOUBLE ROW CULTIVATION MODELS ON THE PRODUCTION OF INNERIE VARIETY OF KIDNEY BEANS IN LOW DRYLANDS : STUDY OF SINGLE ROW AND DOUBLE ROW CULTIVATION MODELS ON THE PRODUCTION OF INNERIE VARIETY OF KIDNEY BEANS IN LOW DRYLANDS - Yosefina Lewar; Ali Hasan; Stormy Vertygo (Politeknik Negeri Lampung., 2023)
The purpose of this study was to examine the best type of cultivaton model in increasing the production of kidney bean seeds of the Inerie variety in low dryland. The research was carried out in April - August 2021 on land owned by farmers in Baumata Village and the Horticulture Laboratory of the State Politani of Kupang. The study used a randomized block design with the factors studied were the cultivation model, namely: M1: Single row (40 x 30 cm), M2: Single row (50 x 30 cm), M3: Single row (60 x 30 cm), M4: Double row (40 cm x 20/30 cm), M5: Double row (50 cm x 20/30 cm), M6: Double row (60 x cm x 20/30 cm), M7: Double row (40 cm x 30/ 30 cm), M: Double row (50 cm x 30/30 cm), M9: Double row (60 cm x 30/30 cm). Each treatment was repeated four times so that there were 36 experimental units. The results showed that the single row and double row cultivation models had a significant effect on the production of Inerie variety of red bean seeds in low drylands. The double row 60 x 20/30 cultivation model gave the best seed production, namely the number of pods, number of seeds and seed weight per plant and plot (3 m2).